2023
DOI: 10.21203/rs.3.rs-2635957/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Please listen to me, I want to know what is wrong with my shoulder”: A qualitative study exploring patients’ expectations and experiences with primary care management.

Abstract: Background: The management of shoulder pain is challenging for primary care clinicians considering that 40% of affected individuals remain symptomatic one year after initial consultation. Developing tailored knowledge translation interventions founded on evidence-based recommendations while also considering patients’ expectations could improve primary care for shoulder pain. The aim of this qualitative study is to explore patients’ expectations and experiences of their primary care consultation for shoulder pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…In one study conducted by our team on shoulder pain, a longer delay for consulting was also reported (Lowry et al., 2023). The delay observed here could also be influenced by the fact that some participants did not believe that their FP could help them, as previously reported (Kannan & Veazie, 2014; Liddle et al., 2007; Lowry et al., 2023). To ensure a favourable management, the actual role of FP and the available therapeutic options they can offer should be better known.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…In one study conducted by our team on shoulder pain, a longer delay for consulting was also reported (Lowry et al., 2023). The delay observed here could also be influenced by the fact that some participants did not believe that their FP could help them, as previously reported (Kannan & Veazie, 2014; Liddle et al., 2007; Lowry et al., 2023). To ensure a favourable management, the actual role of FP and the available therapeutic options they can offer should be better known.…”
Section: Discussionmentioning
confidence: 77%
“…In another qualitative study on knee pain, participants reported delaying consultation because they believed it was normal to experience pain due to ageing and were unaware of the importance of prevention or early management to prevent significant disability (Prasanna et al, 2013). In one study conducted by our team on shoulder pain, a longer delay for consulting was also reported (Lowry et al, 2023). The delay observed here could also be influenced by the fact that some participants did not believe that their FP could help them, as previously reported (Kannan & Veazie, 2014;Liddle et al, 2007;Lowry et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations